Influence of Wastepaper Sludge Ash (WPSA) on Ultimate Flexural and Non-Destructive Test (NDT) results of ultra high performance concrete / Wan Mohd Syahidin Wan Sukri ... [et al.] - Wan Sukri, Wan Mohd Syahidin; Abdul Kudus, Sakhiah; Mustaffa, Nurkamaliah; Sugiura, Kunimoto (2022)
Nowadays, cement is widely used in the construction industry for the development of this modern era, which causes bad effects on the environment and human health. Besides, waste products such as wastepaper are the other problems facing the environment and land field disposal. In this research, the use of WPSA is not only used as an alternative way to save the environment but also to improve concrete strength in UHPC. WPSA has been added in the range of 5% to 15% of the total weight of cement in UHPC. The prisms with a size of 100 mm x 100 mm x 500 mm with a different percentage of WPSA were tested for flexural tests and non-destructive tests (NDT), which measure ultrasonic pulse velocity and rebound. These tests were carried out to evaluate the flexural strength and mechanical properties of WPSA based on NDT testing. The results show the addition of 5%, 10%, and 15% of WPSA, which are 1.96 N/mm2, 2.26 N/mm2, and 2.11 N/mm2 respectively, in UHPC, which causes the lower flexural strength result. At the same time, the UPV test result shows the concrete is of doubtful quality for all specimens. The average pulse velocity of control UHPC is 2397.38 m/s, which is the highest. This result was also followed by a rebound number that represents low compressive strength as compared to the result of the compressive test. The highest average compressive strength is 38 MPa, which represents the control UHPC. At 5% WPSA addition, the compressive strength started to decrease. The addition of 10% and 15% of WPSA causes a more significant drop in compressive strength.